An estimation of vertical transmission of Neospora caninum in dairy cattle, in Khorasan Razavi Province, Iran - Shahidi, M; Maleki, Mohsen; Razmi, G (Journal of the Hellenic Veterinary Medical Society, 2024)
Neospora caninum is an important agent of abortion and reproductive loss in dairy cattle. The objective of this study was to determine the rate of vertical transmission of N.caninum in dairy cattle, KorasanRazavi province, Iran. Two dairy farms with history of Neospora abortion were selected and two hundred -eighty blood samples of dairy cattle in the third trimester of gestation were collected from January 2018 to April 2019. The serum samples of each dairy cattle were examined by an indirect ELISA. At the calving, the colostrum samples of seropositive dams with blood samples of their precolostral calves were collected and again examined by the ELISA method. The seroprevalence of Neospora infection was determined by 16.59% (41/247) in dairy farm 1 and 12.12% (4/33) in dairy farm 2 (P>0.05). In the present study, 100% of precolostral calves born of seropositive dairy cattle had antibodies against Neospora caninum before colostrum ingestion. Based on the seroprevalence of dam and daughter, the vertical transmission was estimated at the highest rate (100%). In conclusion, the results are shown the importance of vertical transmission to remain and contribute to N.caninum infection in two dairy farms.